Collaborative Governance dalam Penyelenggaraan Transportasi Sektor Darat di Provinsi Sulawesi Tenggara - Satyadharma, Maudhy; Susanti, Neni (LITERAKOM: Jurnal Literasi dan Komunikasi, 2024)
The implementation of the transportation sector with various existing problems really requires the application of Collaborative Governance. This research was conducted to analyze the implementation of Collaborative Governance in the implementation of transportation, especially in the land sector of Southeast Sulawesi Province. This research used a type of research with a qualitative approach and the research was carried out from October-December 2023. The results of the research concluded that the implementation of land sector transportation in Southeast Sulawesi Province began through a face-to-face dialogue process between stakeholders, this will give rise to trust building between stakeholders. Apart from that, commitment will be built in the collaboration process which will be born in the form of a joint agreement (MoU) between stakeholders. This series is then continued by a joint understanding by the relevant agencies and will have a temporary impact which is expected to be able to encourage the rules for organizing public transport, both passenger transport (AKDP) and goods transport, as well as road traffic rules to be more adhered to so that safe, comfortable, transportation will be created. safe and sustainable in Southeast Sulawesi Province.but